Overlooked systems in S. Baron-Cohen’s gender research - Terence Rajivan Edward (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
The professor of psychopathology Simon Baron-Cohen claims that males are on average stronger at systematizing than empathizing and females are on average stronger at empathizing than systematizing. Systematizing is defined as the drive to construct or understand systems. In this paper, I observe that Baron-Cohen overlooks certain examples of systems, examples which lead to doubts about his claim.